A Systematic Review for Advancing Inclusive and Sustainable Waste Management in Thailand - Pornarit Chounchaisit; Chumporn Moorapun (My University, 2023)
China's 2018 waste import ban caused Thailand to receive excess waste without proper waste management, causing pollution, overflowing landfills, and exploitation of waste pickers. Using mobile platforms to transform Thailand's recycling industry can improve waste pickers' income and well-being, reduce middlemen and transportation costs, and increase government tax revenue. This can contribute to achieving SDGs 1, 8, and 12, reducing poverty, promoting economic growth and decent work, and promoting sustainable consumption and production.
Keywords: Cleaner production; Consumption; Municipal Solid Waste Management